Hi. First of all the problem at hand:
Identify h and k, then write the equation of the transformed function in the form y - k = f(x - h)
f(x) = 1/x, translated 5 units to the left and 4 units up.
When I check the answers it seems 1/x changes to just x. Why is that? Also, how does the f part of the equation translate? From f(x) = x whatever to y = f(x - h) + k?
Identify h and k, then write the equation of the transformed function in the form y - k = f(x - h)
f(x) = 1/x, translated 5 units to the left and 4 units up.
When I check the answers it seems 1/x changes to just x. Why is that? Also, how does the f part of the equation translate? From f(x) = x whatever to y = f(x - h) + k?